2018
DOI: 10.3389/fcell.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma LAMP-2C Modulates Tumor Growth and Autophagy

Abstract: Autophagy plays critical but diverse roles in cellular quality control and homeostasis potentially checking tumor development by removing mutated or damaged macromolecules, while conversely fostering tumor survival by supplying essential nutrients during cancer progression. This report documents a novel inhibitory role for a lysosome-associated membrane protein, LAMP-2C in modulating autophagy and melanoma cell growth in vitro and in vivo. Solid tumors such as melanomas encounter a variety of stresses in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…Lamp2c is expressed at the highest level in the brain and this high endogenous Lamp2c level has been proposed to mediate lysosomal degradation of RNA in this tissue 36 . Although endogenously expressed at low levels, inflammatory conditions increase Lamp2c levels in B cells 37 and melanoma cells 39 . Strong overexpression of Lamp2c in melanoma 39 and B cells 37 has been reported to inhibit macroautophagy and CMA in these cell types, suggesting potential roles of LAMP2C in these cell types under inflammatory conditions.…”
Section: Male Wtmentioning
confidence: 99%
“…Lamp2c is expressed at the highest level in the brain and this high endogenous Lamp2c level has been proposed to mediate lysosomal degradation of RNA in this tissue 36 . Although endogenously expressed at low levels, inflammatory conditions increase Lamp2c levels in B cells 37 and melanoma cells 39 . Strong overexpression of Lamp2c in melanoma 39 and B cells 37 has been reported to inhibit macroautophagy and CMA in these cell types, suggesting potential roles of LAMP2C in these cell types under inflammatory conditions.…”
Section: Male Wtmentioning
confidence: 99%
“…(3) the transcription factor nuclear factor, erythroid derived 2, such as 2 (NFE2L2/NFR2) regulates expression of Lamp2a, being the NFE2L2 deficiency associated with reduced LAMP2A levels [159]; (4) retinoic acid receptor alpha (RARα) has been found to negatively regulate LAMP2A expression, and the RARα activator all-trans retinoic acid (ATRA) acts as a potent LAMP2A inhibitor [160]; (5) endoplasmic reticulum (ER) stress mediates p38MAPK activation which in turns phosphorylates LAMP2A and promotes CMA, a mechanism termed "ERICA" (ER stress-induced chaperone-mediated autophagy) [161]; (6) Phosphopeptide P140, a fragment of the spliceosomal SNRNP70/U1-70K protein, has been reported to alter the composition of HSPA8/HSC70 complexes and down-regulates LAMP2A expression, thereby reducing CMA [162]; and (7) Unlike LAMP2A, the only LAMP2 isoform that participates in CMA, LAMP2C negatively regulates melanoma growth and survival [163].…”
Section: Are Drugs Targeting Autophagy An Effective Anti-gb Tumor Thementioning
confidence: 99%
“…We then asked the question: what is the effect of overexpression of Foxj2 on the autophagy process at the initiation of meiosis in spermatogenesis? According to the literature, there are three different isoforms of LAMP2 arising from alternative mRNA splicing, known as LAMP2A, LAMP2B, and LAMP2C, which function in different types of autophagy, namely CMA, macroautophagy, and RNautophagy/DNautophagy, respectively [ 23 , 24 ]. We then tested the expression of the isoforms of Lamp2 in the testis and found that the mRNA expression level of Lamp2a in the testes of Stra8-cre; Foxj2 tg/tg mice was significantly higher than that of the WT, while there were no significant differences in the mRNA expression levels of Lamp2b or Lamp2c between the Stra8-cre; Foxj2 tg/tg and WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%